Overcome by faith. (February 2018) - Butler, Amy
This sermon, on Matt 17:1–9, reflects on the aftermath of the 2016 United States election, asking the question of whether or not we, as Christians, will be overcome by fear or by faith. Using the example of Dietrich Bonhoeffer, this sermon argues that we should become what Bonhoeffer in his life's work tried to create: a radical community of Christ that does not allow itself to be overcome either by the fear of the Other, which demagogues among us will always seek to exploit on their path to power, or by the very real fears associated with authentic gospel living, but which instead allow faith to power its every decision.